"This wonderful telegraph" plants, cables, and the wiring of the Sulu Sea, 1898-1903 - Medrano, Anthony D. (2023)
This article thinks with technology to show how gutta-percha plants (Palaquium spp.) and submarine cables were central not only to wiring the Sulu Sea at the turn of the twentieth century but also, and more broadly, to realizing a spatially connected, temporally synced Philippine colony in the age of empire and telegraphy. In doing so, it brings into view the ways in which technology created new kinds of encounters that involved Datu Piang, Datu Rajah Muda Mandi, and Sultan Jamalul Kiram, as well as new kinds of experiences that linked the Sulu Sea to Singapore, the Philippines, and the "American Pacific."
Keywords: Telegraph and telegraphy; Gutta-percha; Sulu sea; Communication -- Technological innovations